Good Practice of School Based Child Friendly (SRA) Islamic Education at SMP Negeri 2 Lamongan - Rosedah Sa’datul Marwah; Kusaeri; Lilik Huriyah (Attanwir : Jurnal Keislaman dan Pendidikan, 2024)
This research discusses the Good Practices of PAI Based on Child-Friendly Schools (SRA), at SMP Negeri 2 Lamongan. The aim of the research is to review three points. First, the role of child-friendly school-based PAI in dealing with cases of bullying, violence or bullying at school. Second, the implementation of child-friendly school-based PAI good practices implemented in schools. Third, the impact of implementing child-friendly school policies on changes in student character. This research uses a qualitative method with a case study approach involving instruments; principal, curriculum representative, PAI teacher, guidance and counseling teacher, and class VII students. This research produces conclusions including the following; (1) The role of PAI has an important role and is very crucial, because it is able to make various contributions to various aspects, especially class VII students as the Alpha generation. (2) Child-friendly school-based PAI good practices have been implemented by integrating indicators of the six components of the child-friendly school guidelines and emphasizing an approach to children's needs and welfare as the main focus. (3) The impact of implementing this policy is that it has a significant impact on various aspects such as life, spiritual, social aspects and overall child-friendly school policies can encourage changes in students' character towards a more positive, responsive and caring attitude towards the surrounding environment.